2014 36th Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2014
DOI: 10.1109/embc.2014.6944948
|View full text |Cite
|
Sign up to set email alerts
|

Increased shoulder abduction loads decreases volitional finger extension in individuals with chronic stroke: Preliminary findings

Abstract: Abstract-The ability to open the paretic hand is greatly affected after a stroke. The loss of especially finger extension has been previously reported during isolated finger movements. However, activities of daily life require the combination of reaching and grasping which will require shoulder abduction. Shoulder abductor activity will result in concurrent elbow, wrist and finger flexion which is also referred to as the flexion synergy. Therefore as part of this study the effect of of shoulder abduction (SABD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 14 publications
0
6
0
1
Order By: Relevance
“…This is very much rooted in the previous work by De Luca and colleagues demonstrating that most of the energy related to motion artifacts is in the frequency range from 0 to 20 Hz (De Luca, 2002; De Luca et al, 2010). However, more recent evidence has shown that after stroke the central nervous system might have adopted an alternative motor control strategy that generates neural oscillation in the alpha range (Lan et al, 2014; Baker et al, 2015). This control strategy may emphasize using neural pathways that produce frequency contents under 20 Hz and hence it was suggested as the potential target for poststroke rehabilitation (Baker et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This is very much rooted in the previous work by De Luca and colleagues demonstrating that most of the energy related to motion artifacts is in the frequency range from 0 to 20 Hz (De Luca, 2002; De Luca et al, 2010). However, more recent evidence has shown that after stroke the central nervous system might have adopted an alternative motor control strategy that generates neural oscillation in the alpha range (Lan et al, 2014; Baker et al, 2015). This control strategy may emphasize using neural pathways that produce frequency contents under 20 Hz and hence it was suggested as the potential target for poststroke rehabilitation (Baker et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, most individuals with chronic hemiparetic stroke have lost such ability due to the stereotypical muscle coactivation patterns between shoulder abductor, elbow flexor, and wrist/finger flexors, commonly referred to as the flexion synergy (Dewald et al, 1995; Sukal et al, 2007; Miller and Dewald, 2012; Lan et al, 2014; Ellis et al, 2016). Due to the expression of the flexion synergy, many individuals find it harder or even impossible to open the hand and/or grasp an object when lifting the paretic arm at the same time (Miller and Dewald, 2012; Lan et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, abnormal flexion of the hand increases as a function of increasing abduction loads [26]. Furthermore, volitional extension of the thumb and fingers is reduced as a function of increasing abduction loads during reaching [32]. Here we present a kinematic/kinetic measurement of maximum hand opening (pentagon area) and grip force as a function of abduction loading to provide a quantitative measurement of the impact of loss of independent joint control on hand function.…”
Section: How Do You Measure/quantify the Effect Of Loss Of Independenmentioning
confidence: 99%